Jamaah Ahmadiyah Indonesia (JAI) Dalam Perspektif Kekerasan Negara: Dua Kasus Dari Surabaya Jawa Timur dan Lombok NTB - Gaffar, Abdul (The Sociology of Islam, 2013)
This study attempts to analyze violence against the Ahmadiyya Community in two area, Surabaya East Java and Lombok NTB conducted by the state through the apparatus, both repressive apparatus such as the police and military and ideological apparatus such as MUI, as well as by the public as a form of direct violence. Various kinds of violence experienced by the Ahmadiyya Community in the two areas, namely East Java governor rule in 2011 has made some Ahmadiyya activities Surabaya became choked up and even some into the vacuum, while in Lombok is more pathetic, the Ahmadiyya Muslim Community has been displaced for seven years after they were expelled from their homes in Gegerung village District Lingsar of West Lombok to Boarding Transito Mataram, NTB. The method used in this study is the method qualitatve research, because research is preface the data collection techniques of observation and interviews conducted in Surabaya and the methods of literature conducted in Lombok. By using the framework of thinking violence theory Johan Galtung, power and knowledge Michael Foucault and the repressive apparatus of the theory and ideological apparatus of Louis Althusser, the study found that the state had committed violence against the Ahmadiyya Community, either directly or indirectly, such as neglect and lack of law enforcement against people who commit violence against the Ahmadiyya Community as experienced by the Ahmadiyya Muslim Lombok, and the MUI fatwa also rules the East Java Governor also encourages the public to direct violence against the Ahmadiyya Community, both in Surabaya and moreover that occurred in West Lombok, West Nusa Tenggara. Kata Kunci: Ahmadiyah, Nagara, MUI, Masyarakat, Kekerasan, Pengusiran.